Polish Experience from 25 Years of the Operation of Special Economic Zones as a Form of Support for the Development of Selected Regions - Malgorzata OFIARSKA (Communications of International Proceedings, 2020)
The study involves an examination and assessment of the period of 25 years of the operation of special economic zones in Poland, using the legal-dogmatic, legal-historical, and empirical methods. Special preferences are applied in these zones, the primary aim of which should be to promote investment and increase employment in economically neglected areas. The intended purpose of the research was successfully achieved, showing that despite several significant changes in the legal regulations regarding the forms of state aid (subsidies, support from a separate special-purpose Zone Fund, tax reliefs and exemptions), special economic zones do not fulfil their basic function, i.e. they are not a mechanism to promote investments involving advanced technologies and associating economic activity with scientific research. Furthermore, the possibilities of extensive development of the zones by expanding their areas have been exhausted, and even some of these areas have not been developed. It was found that these were the main reasons for the radical change in the concept of promoting new investments implemented from 2018 throughout the country and the possibility of granting state aid in this regard in the form of income tax exemptions for a period of 10 to 15 years. The “Polish Investment Zone” thus created did not, however, result in the liquidation of the existing special economic zones, which will exist until the end of 2026. Under the conditions specified by the legislator, an entrepreneur may simultaneously benefit from state aid for investing in both types of zones.
Keywords: Economic Zones; Economic Development; New Investments; State Aid; Tax Privileges.